Diseño de un modelo de gestión administrativa para el desarrollo del turismo comunitario en la comunidad Kichwa “Sinchi Pura” – Parroquia Talag - Cantón Tena-Provincia Napo. - Balseca Beltrán, Carla Elizabeth (2013)
Ecuador has seen tourism as a great opportunity to generate significant revenue and help with its economy, offering diverse forms of tourism among these we have the communitarian Tourism. The Communitarian Tourism is an economic activity practiced by members of a community whose offering product is coexistence, customs and beliefs exchange between natives and visitors. Its objectives are ancestral identity and community natural resources safeguarding.